Analysis of spatio-temporal allocation of snow cover on the territory of Vinnytsia region - Nedostrelova, Larysa; Nedostrelov, Maksym (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Formulation of the problem. Snow cover has a great influence on the climate, relief, hydrological and soil-forming processes, plant and animal life. It protects the soil from deep freezing and preserves winter crops, absorbs nitrogenous compounds, thus fertilizing the soil, adsorbs atmospheric dust and cools the surface layers of the air. Snow cover and its duration are social and economic important and affect the environment. Snow-related difficulties are a dangerous factor in the human environment, and more attention should be paid to the impact of snow on the economy or its great value as a natural resource. The investigation of the spatial distribution and temporal variability of the snow cover is an urgent and important issue, especially in the conditions of modern climate changes. The purpose of the article is to establish the characteristics of the spatio-temporal distribution of snow cover in the territory of Vinnytsia region for the period 1996-2018 and the features of its characteristics at the beginning of the XXI century. Methods. The data of daily meteorological observations on the height of the snow cover at the stations of the Vinnytsia region were used as the initial information. To characterize the height of the snow cover, its average values are calculated not for months, but for decades of winter months. Decadal heights and their repeatability by decade were calculated for each station for the period from 1996 to 2018 based on data on the distribution of snow cover height. Results. The analysis of the spatio-temporal distribution of snow cover for the period 1996-2018 makes it possible to describe certain features of the formation of snow cover in the territory of Vinnytsia region: the snow cover in Vinnytsia region is formed in the third decade of October, with the exception of the Vinnytsia and Khmilnyk stations, where the appearance of snow cover begins in the second decades of October; disappearance occurs in the third decade of April throughout the region; decadal heights of snow cover have the maximum repeatability in the gradation from 0 to 5 cm; average decadal heights with the largest values from 10 to 13 cm were found in January and February at the stations of Bilopillia, Vinnytsia and Khmilnyk; the formation of stable snow cover on the territory of Vinnytsia region occurs in the second decade of November; the destruction was recorded from the second decade of March to the first decade of April. Scientific novelty and practical significance. The article provides an analysis of the distribution of snow cover and features of its formation at the end of the 20th and the beginning of the 21st centuries on the territory of the Vinnytsia region. The snow cover has a significant impact on the branches of Ukraine’s economy. Agriculture is the most sensitive to the features of snow cover formation, especially when it comes to overwintering of winter crops. One of the main agrometeorological factors that determine the overwintering of winter crops is the height of the snow, its spatial and temporal variability, the period of appearance and disappearance of the snow cover. We believe that our investigation can be used to clarify the forecast of the yield of winter crops in Vinnytsia.